A KNOWLEDGE MANAGEMENT MODEL FOR LOCAL - KINYANJUI, ANDREW K. (My University, 2011)
Globalization and the development of global city regions that are home to millions of inhabitants have put unprecedented pressure on cities and their local governments. A lot more is expected of cities and their local governments by their citizenry. It is at the local government level where most government services and products are provided and rendered. Local governments in South Africa are no different and face various service delivery challenges. Research has shown that there is significant knowledge within local government but it is not being optimally utilised. It has been argued that managing knowledge properly can significantly enhance service delivery by attaining higher levels of effectiveness and efficiency. However, existing knowledge management models such as the Leibowitz model may only partially address the needs of local government. The purpose of this study is to explore how local government in South Africa conceptualises and implements KM. The results of the study will be used to develop a framework that would be generally applicable to similar local government KM initiatives, in order to enhance the capacity of local government to utilise knowledge to address its service delivery challenges
MM - P&DM
Keywords: Knowledge management; Local authorities